Islamic Boarding School and Journalistic Da'wah (Da'wah Writing Campaign Study) - Asmar, Afidatul; M. Said, Nurhidayat; Siagian, Haidir Fitrah (Jurnal Kajian Manajemen Dakwah, 2023)
This study aims to investigate the role of pesantren in the da'wah writing campaign through journalistic media. Pesantren, as traditional Islamic educational institutions in Indonesia, have great potential in disseminating da'wah messages to the public through various media platforms. Through a case study approach, this research will analyze how pesantren use journalistic media as a tool for da'wah writing campaigns. This research will use a qualitative method by conducting in-depth interviews and participatory observations in several pesantren that are active in da'wah writing campaigns through journalistic media. The collected data will be analyzed using a content analysis approach to identify the main themes and strategies of da'wah writing used by pesantren in their campaigns.The results of this study are expected to provide a deeper insight into the role of pesantren in the da'wah writing campaign through journalistic media. This research is also expected to provide an understanding of how pesantren adapt their da'wah messages to different media contexts. The results of this study are expected to be an important contribution in the development of more effective and impactful da'wah strategies through journalistic media.